Clinical Characteristics of Intraocular Lens Dislocation in Chinese Han Populations - Qi Fan; Xiaoyan Han; Xiangjia Zhu; Lei Cai; Xiaodi Qiu; Yi Lu; Jin Yang (Journal of Ophthalmology)
Purpose. To investigate the clinical characteristics of patients with intraocular lens (IOL) dislocation after IOL implantation in Chinese Han populations. Methods. The medical records of patients with IOL dislocation were retrospectively reviewed from January 2007 to December 2017, and a total of 312 patients (male: 231, female: 97) (328 eyes) were included in this study. The axial length (AL), IOL power, and the time interval between cataract surgery and IOL dislocation as well as the ocular conditions associated with IOL dislocation were recorded. The IOL dislocation was classified and graded based on its relationship with the capsule and the position of the dislocated IOL. Results. The mean time between original cataract surgery and IOL dislocation was 5.63 ± 5.13 years; IOL dislocation occurred in up to 56.1% (184 eyes) of the eyes within 5 years. Trauma was found in 136 eyes (41.5%); pars plana vitrectomies were performed in 61 eyes (18.6%), and high myopia was detected in 108 eyes (32.9%). A total of 243 eyes (74.1%) had out-of-the-bag IOL dislocations, while 85 eyes (25.9%) had in-the-bag IOL dislocations. There was a statistically significant difference in the constituent ratio of trauma between in-the-bag dislocation and out-of-the-bag dislocation (Pearson’s chi2 = 33.3992, P<0.001); ocular blunt traumas were significantly higher in in-the-bag dislocations, while open-globe injuries were significantly higher in out-of-the-bag dislocations. A statistically significant difference was found for the ratio of patients with AL longer than 30 mm between in-the-bag dislocation and out-of-the-bag dislocation (Pearson’s chi2 = 9.7355, P<0.002). Conclusions. In Chinese Han populations, the most common IOL dislocation is out-of-the-bag dislocation; the most common risk factors were trauma, long axial length, and eyes undergoing pars plana vitrectomy; a minimum follow-up of 5 years is suggested for IOL dislocation-predisposed eyes undergoing cataract surgery.